1987
DOI: 10.1038/329727a0
|View full text |Cite
|
Sign up to set email alerts
|

Corticofugal feedback influences the generation of length tuning in the visual pathway

Abstract: In the feline visual system, neurons exhibiting sensitivity to the length of a moving contour were first observed in the cortex and described as 'hypercomplex cells'. In these cells an increase in stimulus length beyond an optimal value leads to a rapid decline in response. This decline has been attributed to an intracortical inhibitory input which may be driven by layer VI cells with very long receptive fields. It is now clear, however, that cells in the dorsal lateral geniculate nucleus (dLGN), exhibit a deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(202 citation statements)
references
References 14 publications
8
190
2
Order By: Relevance
“…Thus, the level of cortical activity could regulate the sleep-related activity of thalamic neurons via mGlu1 receptor activation (Hughes et al 2002). However, it is also highly likely that there is a contribution from corticofugal systems to sensory responses in vivo, and this has been investigated over many years (Tsumoto et al 1978;Murphy & Sillito 1987;Sillito et al 1994) (and see Sherman & Guillery (2002) and Sillito & Jones (2002)). It has been speculated that the in uence of the cortical input may operate via NMDA receptors or mGlu receptors (Koch 1987;Sherman & Guillery 2000), largely because transmission via these receptor types would allow the non-linear ampli cation of excitatory inputs mediated via, for example, AMPA receptors.…”
Section: Sensory Responses Of Thalmic Relay Neurons In Vivo: Recruitmmentioning
confidence: 99%
“…Thus, the level of cortical activity could regulate the sleep-related activity of thalamic neurons via mGlu1 receptor activation (Hughes et al 2002). However, it is also highly likely that there is a contribution from corticofugal systems to sensory responses in vivo, and this has been investigated over many years (Tsumoto et al 1978;Murphy & Sillito 1987;Sillito et al 1994) (and see Sherman & Guillery (2002) and Sillito & Jones (2002)). It has been speculated that the in uence of the cortical input may operate via NMDA receptors or mGlu receptors (Koch 1987;Sherman & Guillery 2000), largely because transmission via these receptor types would allow the non-linear ampli cation of excitatory inputs mediated via, for example, AMPA receptors.…”
Section: Sensory Responses Of Thalmic Relay Neurons In Vivo: Recruitmmentioning
confidence: 99%
“…This has been established most thoroughly in the visual system, where lower (primary) areas receive sensory input and higher areas adopt a multimodal or associational role. The neurobiological notion of a hierarchy rests upon the distinction between forward and backward connections (Rockland & Pandya 1979;Murphy & Sillito 1987;Felleman & Van Essen 1991;Sherman & Guillery 1998;Angelucci et al 2002). This distinction is based upon the specificity of cortical layers that are the predominant sources and origins of extrinsic connections.…”
Section: Hierarchical Models In the Brainmentioning
confidence: 99%
“…Murphy and Sillito (1987) showed that cortical feedback causes signi cant length-tuning in cat LGN cells. As in cortical endstopping, the response to a line grows rapidly as a function of line length and then abruptly declines for longer lines.…”
Section: Resonant Dynamics During Brightness Perceptionmentioning
confidence: 99%